«The Muslim Brotherhood» and prospects of the political process in contemporary Egypt - M. Z. Razhbadinov (Vestnik MGIMO-Universiteta)
The article focuses on the role of the moderate islamists movement «The Muslim Brotherhood» in current political situation in Egypt. «The Muslim Brotherhood» is the most organized and powerful force in contemporary Egypt. The author deals with ideology and strategy of the movement, the relationship with other political forces, internal differences and opportunities in power. He concludes that the «Cairo effect» caused long overdue tectonic shift in the Arab region. Egypt has begun its move to build up a democratic state but with their own specifics. The future situation in the country will depend on the relationship «The Muslim Brotherhood» with the army and political secular powers. The country has just started to move in the way that Turkey did a few decades ago